EFFECTIVENESS OF DIGITAL PLATFORMS AS FOOD AND BEVERAGE MARKETING MEDIA DURING THE COVID-19 PANDEMIC - Ira Nur Hidayah; Nur Fadhilatur Rohmah; Muchammad Saifuddin (Airlangga Journal of Innovation Management, 2021)
Covid-19 pandemic disrupted business practices worldwide, especially in food and everage sector. Not a few business actors in this sector closed their business due to declining sales during pandemic. In responding to this global effect, business actors are not only encouraged to adapt. Still, they must also think of practical steps to stabilize sales as before through creative and innovative digital marketing strategies. Data collected by interviews and literature study to provide an in-depth analysis of condition of food and beverage during Covid-19 pandemic and provide education about digital marketing strategies that business actors can apply to increase food and beverage sales during Covid-19 pandemic. The results showed that social media such as Instagram, Facebook, Twitter, and Whatsapps were effective in marketing food and beverage products. In addition, Shopeefood e-commerce platform and food delivery applications such as GrabFood and GoFood also play a significant role in success of food and beverage marketing and sales and can support government regulations to stay at home during the Covid-19 pandemic.